Ferrocene- and fullerene[60]-containing liquid-crystalline materials - Chuard, Thierry; Deschenaux, Robert (My University, 1998)
A review with 22 refs. showing the versatility of ferrocene and fullerene for the design of thermotropic liq.-cryst. materials: (i) the electrochem. properties of the ferrocene-ferrocenium system were exploited to design redox-active metallomesogens; (ii) ferrocene-contg. side-chain liq.-cryst. polysiloxane and polymethacrylates were synthesized by grafting a mesomorphic vinyl-ferrocene monomer onto com. available polysiloxane and by free-radical polymn. of mesomorphic methacrylate-ferrocene monomers, resp.; (iii) a 1st-generation ferrocene-contg. liq.-cryst. dendrimer was synthesized; and (iv) liq.-cryst. fullerene (10) and mixed fullerene-ferrocene (11) derivs. were obtained by functionalizing the C60 core with a twin cholesterol moiety. [on SciFinder(R)]
Keywords: review liq crystal ferrocene fullerene